Funding women entrepreneurs : How to empower growth - Fackelmann, Surya; De Concini, Alessandro; European Investment Bank; European Investment Bank (European Investment Bank, 2020)
Intervention is needed to improve women-led companies$1 (Baccess to finance. In a recent study, EIB$1 (Bs InnovFin Advisory assessed the availability of finance for women-owned and managed companies in Europe as compared to the United States. While women-led companies account for only a small portion of financing deals and investment flows, their share is growing. Nevertheless, structural inequalities and persistent biases continue to distort the funding environment. The study puts forth a number of innovative finance and policy recommendations. Restarting the EU economy after the coronavirus pandemic provides a unique opportunity to tackle gender barriers to finance.s
Knowledge Unlatched
English
Keywords: Finance; Business & Economics; Finance